ME-105 Manufacturing Practice-Introduction to Electroplating - Sankara Rao, Dr. Lakkoju (Main Workshop, IIT (BHU), Varanasi, 2016)
This video gives an introduction to the electroplating and shows the step by step procedure to make copper and nickel electroplating on a mild steel rod.
This video gives an introduction to the electroplating and shows the step by step procedure to make copper and nickel electroplating on a mild steel rod
Keywords: electroplating; Manufacturing Practice; copper and nickel; mild steel rod